2015
DOI: 10.18553/jmcp.2015.21.6.479
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Medication Adherence Barriers Among Patients with Cardiovascular Risk Factors

Abstract: BACKGROUND: Many patients experience barriers that make it difficult to take cardiovascular disease (CVD)-related medications as prescribed. The Cardiovascular Intervention Improvement Telemedicine Study (CITIES) was a tailored behavioral pharmacist-administered and telephone-based intervention for reducing CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 30 publications
5
27
2
2
Order By: Relevance
“…National studies of CVD prevention find that lack of support directly contributes to an inability to engage in prevention-related behavior (31) . Similarly, previous analyses from this study cohort found that lacking someone to assist tracking medications is associated with higher medication barriers (45) . For men, being married or cohabiting appears to be an important factor in lowering CVD risk (59) .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…National studies of CVD prevention find that lack of support directly contributes to an inability to engage in prevention-related behavior (31) . Similarly, previous analyses from this study cohort found that lacking someone to assist tracking medications is associated with higher medication barriers (45) . For men, being married or cohabiting appears to be an important factor in lowering CVD risk (59) .…”
Section: Discussionsupporting
confidence: 72%
“…Weight, height, and blood pressure were also measured at the baseline visit. Participants were also asked to complete the Rapid Estimate of Adult Literacy in Medicine (REALM) test (45) . We dichotomized the REALM scores into a binary measure identifying low literacy (equivalent to an eighth grade reading level) using a total score <60 as has been done previously (45) .…”
Section: Methodsmentioning
confidence: 99%
“…These eight trials started recruitment between 2011 and 2014. Of these trials, one included dyads of patients and caregivers (Van Houtven et al, 2014), four targeted cardiovascular disease risk factors including obesity and hypertension (Jackson et al, 2016;Oddone et al, 2017;Voils et al, 2014;Voils et al, 2016;Zullig et al, 2014;Zullig et al, 2015), one addressed smoking cessation (Wilson et al, 2016), one addressed emergency department follow-up (Hastings et al, 2014), and one addressed osteoarthritis of the knee and hip (Allen et al, 2012; Table 1). The mean participant age was 57.7 years for women and 65.9 years for men.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, those who were not employed increased risk 1.32, or did not have someone to help with tasks increased risk 1.66 for nonadherence in patients with cardiovascular risk factors. [13] There are defined living in a village compared with a city, dissatisfaction with treatment, forgetfulness, fear of getting used to the medication, adverse effects are associated with lower medication adherence. Evaluating health status as very good, good, or poor compared with excellent also was found associated with lower adherence.…”
Section: Discussionmentioning
confidence: 99%